Patient-derived tumor xenograft models for melanoma drug discovery. (1st September 2016) - Harris, Antoneicka L.; Joseph, Richard W.; Copland, John A.
ABSTRACT: Introduction : Cutaneous metastatic melanoma (MM) is an aggressive form of skin cancer, with treatment providing cures to a minority of patients. The multiple risk factors that contribute to MM development suggest that cutaneous melanomas embody a repertoire of altered genetic events requiring studies to better understand its biology in order to develop novel therapies. Areas covered : Patient-derived tumor xenograft (PDTX) mouse models are noted to be superior for novel drug discovery and tumor biology studies due to their ability to maintain tumor heterogeneity and their use as real-time individualized patient models. In this review, the authors highlight the utility of PDTX models in advancing treatment options for patients with MM by creating invaluable preclinical models that exhibit patient-relevant treatment outcomes. Expert opinion : There is a strong necessity to reassess current approaches in which preclinical experiments are designed and executed in order to minimize unwarranted clinical trials. With rigorously performed preclinical studies, PDTX models have the capability to effectively confirm or deny drug effective outcomes. The ability to do this, however, will demand better aids to guide experimental design, the redefining of preclinical efficacy, and the understanding that these models should be viewed as complementary to other drug prediction and efficacy tools.